The role of research institutions in seed-related disaster relief: Seeds of Hope experiences in Rwanda - Buruchara, Robin Arani; Sperling, L.; Ewell, P.; Kirkby, Roger A. (Wiley, 2002)
The article describes the efforts of a coalition of agricultural research centres, Seeds of Hope (SOH) in the rebuilding of Rwanda, after the genocide and war of 1994. Research involvement in emergency relief and rehabilitation was unusual at the time and SOH had to forge its unique complementary role. Focusing on crop and variety development and conservation it: provided technical advice to relief agencies on seed procurement; used its baseline ken to assess the effects of war on seed diversity and seed security; made preparations to restore specific germplasm (which, fortunately, proved unnecessary) and spent substantial effort on rebuilding human resource capacity in research as well as basic scientific facilities. The involvement of SOH highlighted the critical, yet very different, roles for research during emergency versus rehabilitation periods and demonstrated the cost effectiveness of building in a diagnostic component — before massive seed or germplasm distributions are programmed.